Prognostic relevance of regional lymph-node distribution in patients with N1-positive non-small cell lung cancer: a retrospective single-center analysis - Eichhorn, Florian; Klotz, Laura Valentina; Muley, Thomas; Kobinger, Sonja; Winter, Hauke; Eichhorn, Martin E. (Lung cancer, 2019)
Objective - Lymph node (LN) metastases predict survival in patients with non-small cell lung cancer (NSCLC) treated with curative surgery. Nevertheless, prognostic differences within the same nodal (N) status have been reported. Consequently, the International Association for the Study of Lung Cancer (IASLC) proposed to stratify patients with limited nodal disease (pN1) from low (pN1a) to high (pN1b) nodal tumor burden. This study aimed to validate the IASLC proposal in a large single-center surgical cohort of patients with pN1 NSCLC. - Material and Methods - Data from 317 patients with pN1 NSCLC treated between January 2012 and December 2016, were retrospectively analyzed. Associations between distribution of LN metastases and survival were analyzed for different classification models—toward nodal extension (pN1a: one station involved; pN1b: multiple stations involved) and toward location (pN1 in the hilar [LN#10/11] or peripheral zone [LN#12-14]). - Results - Tumor-specific survival (TSS) in the entire pN1 cohort was 67.1% at five years. Five-year TSS rates for pN1a and pN1b patients were comparable (67.6% vs. 66.5%, p=0.623). Significant survival differences from pN1a to pN1b were observed only in patients with adenocarcinoma histology and completed adjuvant chemotherapy (5-year TSS: pN1a, 80.4% vs. pN1b, 49.6%; p=0.005). TSS for LN metastases in the hilar zone/peripheral zone or in both zones was 68.2% and 59.9%, respectively (p=0.068). In multivariate analysis, adjuvant chemotherapy, squamous cell histology, and nodal disease limited to one zone nodal disease were identified as independent beneficial prognostic factors (p<0.05). - Conclusion - pN1 in only one region (hilar or lobar) was associated with better outcome than metastatic affection of both regions after surgery and adjuvant therapy. A stratification towards single (pN1a) and multiple (pN1b) N1-metastases was found of prognostic relevance only in adenocarcinoma. Prospective multicenter analysis of prognostic subgroups in N1 NSCLC is required to evaluate its clinical impact for consideration in future TNM classification.
Gesehen am 27.02.2020